The game in the identity and autonomy of the child - Nazario Urbina, Mayra Russel Del Carmen (2020)
The present research work entitled The game as a strategy for the development of identity and autonomy in children under 6 years - Educational institutions at the initial level Chiclayo, 2019. Its main objective was to promote the development of the identity and autonomy of minor children 6 years through game strategies. With a pre-experimental research design, taking as a sample a total of 75 children, to whom a data collection instrument was applied, this being a checklist, which was validated in the opinion of an expert with a level of reliability of 0.889. As a main conclusion, it was verified that the variables of the game as a strategy had a significant influence on the development of identity and autonomy in children under 6 years of the IEP "Angelitos de María and Emblematic and Inclusive Institución Educativa "Karl Weiss". The type of research is quantitative since the analysis and measurement of the information requires intensive and deep studies through the collection of the pre and posttest. An applied preexperimental design is used, whose results were able to reverse the data found at the beginning; contributing to the general objective having as stimulus the game strategies as a significant ally in the development of identity and autonomy.